Determination of phenolic acids and flavonoids in Rhinacanthus nasutus (L.) kurz by high-performance-liquid-chromatography with photodiode-array detection and tandem mass spectrometry. (January 2015) - Huang, R.T.; Lu, J.F.; Inbaraj, B. Stephen; Chen, B.H.
Highlights: Phenolic acids and flavonoids determined in Rhinacanthus nasutus by HPLC-PAD–MS/MS. High extraction yield of phenolic acids and flavonoids obtained with 30% ethanol at 60 °C. A C18 column with gradient system separated 20 phenolic acids and 3 flavonoids. Separated compounds identified by photo-diode-array and MS–MS detection. Compounds quantified by internal standards and method validated by quality control data. Abstract: The variety and content of phenolic acids and flavonoids in a Chinese herb Rhinacanthus nasutus were determined by developing an HPLC method coupled with photodiode-array-detection and tandem-mass-spectrometry. A high yield of phenolic acids and flavonoids was obtained using 30% ethanol-in-water and shaking in 60 °C water-bath for 3 h. By employing a C18 column and gradient mobile phase of 0.1% formic acid-in-water and acetonitrile, a total of 20 phenolic acids and 3 flavonoids were separated within 45 min with detection at 280 nm, flow rate at 0.8 mL/min and column temperature at 35 °C. Internal standards vanillic acid and quercetin were used for quantitation of phenolic acids and flavonoids in R.   nasutus, respectively, which included caffeic acid derivatives (6.40 mg/g), quercetin derivatives (4.43 mg/g), ferulic acid derivatives (3.20 mg/g), p -coumaric acid derivatives (1.63 mg/g), sinapic acid hexoside (1.11 mg/g), kaempferol-3- O -rutinoside (1.02 mg/g), hydroxycinnamic acid derivatives (0.44 mg/g) and protocatechuic acid (0.39 mg/g).